PELATIHAN BAHASA INGGRIS BAGI GURU TK DI KALURAHAN DUKUH, KECAMATAN MOJOLABAN SUKOHARJO - Nunun Tri Widarwati; Betty Gama; Ardian Prima Putra (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Nunun Tri Widarwati, Betty Gama, Dan Ardian Prima Putra. Pengabdian kepada masyarakat kompetitif Klaster ( PMKK ) Taman Kanak-kanak Desa Dukuh I dan Taman Kanak-Kanak Desa Dukuh II. Universitas Veteran Bangun Nusantara Sukoharjo. 2015The teaching ability of Mr / Ms (TANPA SPASI) kindergarten teacher in Dukuh village in English for children has no basic training at all and in communicating with English is considered very less (SENTENCE IS REPAIRED AGAIN). This is because Mr. / Ms teacher does not have an English education background. Adult English is now very important, because it becomes a global language that must be mastered in a global society.  Therefore it is very important to teach and introduce English to children as early as possible. In order for them to know and enjoy English. Father / Mother kindergarten teacher in hamlet village need the training of teaching English for Kindergarten children so that they are happy and happy to learn English. Therefore, to improve thequality of partner human resources, the activities of community service are conducted in the form of: English Short Course Program, Procurement Program of English learning media in the form of English for young learner teaching book, Language Competence Strengthening Program and English teaching program for kindergarten children.Keywords: Training, Kindergarten Teachers, English